An industry 4.0 approach to large scale production of satellite constellations. The case study of composite sandwich panel manufacturing. (March 2022) - Eugeni, M.; Quercia, T.; Bernabei, M.; Boschetto, A.; Costantino, F.; Lampani, L.; Spaccamela, A. Marchetti; Lombardo, A.; Mecella, M.; Querzoni, L.; Usinger, R.; Aliprandi, M.; et al.
Abstract: In recent years the so-called New Space Economy or Space 4.0 paradigm has seen a number of new commercial players entering the satellite industry and creating completely new business models, most of which based on very large constellations consisting of several hundreds or even thousands of satellites. The production of the high number of satellites involved in modern mega-constellations is bringing in the space industry the necessity of improved and optimized manufacturing approaches suitable for serial production, i.e., standard environment/high number of platforms. In this framework, the adoption of Industry 4.0 methodologies within the space industry will lead to a significant improvement and optimization of the whole Manufacturing Assembly Integration and Testing (MAIT) cycle. The main aim of Industry 4.0 is the creation of intelligent factories where manufacturing technologies are upgraded and transformed by Cyber-Physical Systems (CPSs), the Internet of Things (IoT), Cloud Computing and Big Data Analytics with predictive monitoring features. Main element of the Industry 4.0 approach is the synergic use of embedded sensing technologies in the frame of intelligent production processes, fostering a radical evolution of the industrial values chains, production value chains, and business models. In the present work, a possible application of the Industry 4.0 concepts to space industry is presented and discussed in terms of applicability and obtainable advantages. As a case study, the composite sandwich panel manufacturing line of RUAG Space is considered. Particular focus will be given to the development of a CPS, by establishing a control network of sensors (e.g. temperature, location, load) over a targeted MAIT process. Highlights: The implementation of Industry 4.0 logics to satellite industry is considered. The composite panel manufacturing MAIT process is considered as case-study. A CPS of the composite panel manufacturing MAIT process is built. AI logics are considered in order to improve the monitoring and control of the selected process. The benefit of Smart Manufacturing for satellite industry are discussed.